2013
DOI: 10.1371/journal.pone.0063538
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Ammonia Causes Significant Plant Growth Inhibition

Abstract: Many and complex plant-bacteria inter-relationships are found in the rhizosphere, since plants release a variety of photosynthetic exudates from their roots and rhizobacteria produce multifaceted specialized compounds including rich mixtures of volatiles, e.g., the bouquet of Serratia odorifera 4Rx13 is composed of up to 100 volatile organic and inorganic compounds. Here we show that when growing on peptone-rich nutrient medium S. odorifera 4Rx13 and six other rhizobacteria emit high levels of ammonia, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 43 publications
(68 reference statements)
1
53
0
Order By: Relevance
“…Recently, Weise et al . () revealed that rhizobacteria may emit high levels of ammonia, which during co‐cultivation in compartmented Petri dishes caused alkalization of the neighboring plant medium and subsequently reduced the growth of A. thaliana (Weise et al ., ). However, the observed antifungal effect of volatiles emitted by Collimonas strains in this work was not due to ammonia emission and changes in the pH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Weise et al . () revealed that rhizobacteria may emit high levels of ammonia, which during co‐cultivation in compartmented Petri dishes caused alkalization of the neighboring plant medium and subsequently reduced the growth of A. thaliana (Weise et al ., ). However, the observed antifungal effect of volatiles emitted by Collimonas strains in this work was not due to ammonia emission and changes in the pH.…”
Section: Discussionmentioning
confidence: 99%
“…Although strong growth promotion – which turned out to be partly due to CO 2 emission (Kai & Piechulla, ) – was confirmed in many cases, these early studies also reported drastic growth inhibition, phytotoxic effects, and even plant killing within a few days (Vespermann et al , ; Blom et al , ). The volatiles responsible were identified mainly as inorganic compounds; for example, hydrogen cyanide (HCN; Blom et al , ) or ammonia (Weise et al , ). Later work demonstrated that some organic volatiles were phytotoxic as well, especially when applied in high (micromolar to millimolar) concentrations.…”
Section: Direct Effects Of Bacterial Volatiles On Plant Healthmentioning
confidence: 99%
“…The role that ammonia might play in bacterial–plant interactions (Table ) is still poorly understood and not often considered or investigated (Table S3). Kai et al () and Weise et al () clearly demonstrated that ammonia as a component of the bacterial volatile mixture led, via alkalization of the growth medium, to drastic phytotoxic effects on A. thaliana . This negative effect was mostly observed when bacterial isolates were grown on peptide‐rich medium suggesting that degradation of amino acids was the source of ammonia formation.…”
Section: Biological Effects Of Microbial Inorganic Volatile Compoundsmentioning
confidence: 99%